Mineral Policies - Stamenkovic, Marko (punctum books, 2022)
Mineral Policies provides a record of an art residency organized by ZETA Center for Contemporary Art in the mining region of Bulqiza in northeastern Albania, where four artists and activists from Albania, Blerta Hoçia, Diana Malaj, Pleurad Xhafa, and Ergin Zaloshnja, created a collective body of works in close proximity with the local miners, while still maintaining their own discrete sphere of action. This residency followed by a public exhibition, Each Strike Leads to the Next, featuring video works produced during the residency as well as a series of object, curated by Vincent W.J. van Gerven Oei, director of the Department of Eagles in Tirana. This publication includes documentation of the residency and the exhibition, as well the record of a public discussion between curator Van Gerven Oei, former Minister of Finance Arben Malaj, mining engineer Genc Myftiu, and mining worker Bardhul Alla, moderated by cultural journalist Elsa Demo and an interview of cultural theorist Jonida Gashi and Van Gerven Oei with the artists. Mineral Policies documents an important attempt of present-day Albanian artists to reflect on and align themselves with workers and labor activities within a political climate in which neoliberal extractivism and mafia-controlled local and national government have seriously compromised modes of solidarity and survival.